The effect of polymorphic metabolism enzymes on serum phenytoin level - GÜNEY, AHMET İLTER; ONAT, FİLİZ; ULUCAN, KORKUT (SPRINGER-VERLAG ITALIA SRL, 2015)
Phenytoin has a widespread use in epilepsy treatment and is mainly metabolized by hepatic cytochrome P450 enzymes (CYP). We have investigated CYP2C9*2, CYP2C9*3, CYP2C19*2 and CYP2C19*3 allelic variants in a Turkish population of patients on phenytoin therapy. Patients on phenytoin therapy (n = 102) for the prevention of epileptic seizures were included. Polymorphic alleles were analyzed by restriction fragment length polymorphism method. Serum concentrations of phenytoin were measured by fluorescence polarization immune assay method. The most frequent genotype was detected for CYP2C9 wild-type alleles (78.43 %), whereas CYP2C19*2/*2 (5.88 %) was the least frequent genotype group. According to the classification made with both enzyme polymorphisms, CYP2C9*1/*1-CYP2C19*1/*1 (G1: 41.17 %) genotype group was the most frequent whereas CYP2C9*1/*2-CYP2C19*1/*3 (G7: 0.98 %) was the least frequent one. The highest mean phenytoin level (27.95 +/- A 1.85 A mu g/ml) was detected in the G8 genotype group (CYP2C9*1/*3-CYP2C19*2/*3) and the G1 genotype group showed the lowest mean phenytoin level (7.43 +/- A 0.73 A mu g/ml). The mean serum concentration of phenytoin of the polymorphic patients with epilepsy was higher than that for the wild-type alleles both in the monotherapy and polytherapy patients. These results show the importance of the genetic polymorphism analysis of the main metabolizing enzyme groups of phenytoin for the dose adjustment.
Keywords: Epilepsy; Phenytoin; Pharmacogenomics; Pharmacokinetics; Pharmacotherapy; Metabolism enzyme; JAPANESE EPILEPTIC PATIENTS; GENETIC-POLYMORPHISM; ANTIEPILEPTIC DRUGS; CYTOCHROME P4502C9; CYP2C SUBFAMILY; PHARMACOKINETICS; HYDROXYLATION; FREQUENCIES; POPULATION; VARIANTS